DIAGNOSTIC AND THERAPEUTIC APPROACH TO VASCULAR ACUTE ABDOMEN WITH EMPHASIS ON ACUTE MESENTERIC ISCHEMIA: A BIBLIOGRAPHICAL REVIEW. - Brito, Paulo Roberto da Silva (2024)
Acute vascular abdomen is a serious clinical condition that occurs when blood flow to the abdominal organs rapidly decreases, potentially causing ischemia and tissue necrosis. Acute mesenteric ischemia (AMI) is a complex form of this syndrome, characterized by sudden obstruction of the mesenteric arterial or venous circulation, resulting in indirect perfusion of the small intestine and subsequent ischemia. Methodology: The research was conducted by accessing online scientific databases such as Google Scholar, National Library of Medicine (PubMed), Virtual Health Library (BVS), and Scientific Electronic Library Online (SCIELO). Keywords related to Acute Vascular Abdomen, Acute Mesenteric Ischemia, Diagnosis, Treatment, Revascularization, and Intestinal Necrosis were used for article selection. Results: AMI is a serious condition that can manifest suddenly with intense abdominal pain disproportionate to physical examination findings, potentially progressing to signs of peritonitis. Risk factors include cardiac and aortic diseases. Diagnosis is challenging and involves measuring serum lactate levels, laboratory findings such as leukocytosis, and imaging changes on abdominal radiography and computed tomography. Angiography may be necessary in specific cases. Treatment includes mesenteric revascularization, surgery to remove necrotic segments, and postoperative support. The morbidity and mortality associated with AMI are high, with the time between symptoms and treatment being a crucial prognostic factor. Final Considerations: AMI is a complex clinical condition that requires immediate diagnosis and treatment. Early detection is crucial due to rapid progression to intestinal necrosis and sepsis. Computed tomography is the most accurate method, while mesenteric angiography confirms the diagnosis. Treatment aims to restore intestinal blood flow through angioplasty, stenting, or surgery, along with intensive support to correct disturbances and prevent complications.